ANALYZING CLIENT-SIDE ENCRYPTION IMPLEMENTED IN CRYPTDB - Mira Maisura (UIN Ar-Raniry, 2018)
Client side encryption has become one of the choice for data security in outsourced database as it is believed to provide more security than the server side encryption. It allows users to protect their data and prohibit access to that data from unauthorized user. Here, key use for encryption and decryption are all belong and known only to the user. On the other words, data stored in the database are all in encrypted form. CryptDB, a new cryptographic technique, where the system acts as a proxy to protect the communication between the application server and database server, implementing the idea. The aim of this study is to look into more detail about the encryption scheme implemented in CryptDB in 2 different case study, using SEARCH command with the condition given. The result of the study will present how the statement change with the act of proxy, and the encryption scheme implemented here.